FACEBOOK SEBAGAI SARANA PUBLIKASI HASIL PEMBELAJARAN - Utami, Citra Dewi (Institut Seni Indoensia Surakarta, 2018)
The learning process is an interactive activity that occurs between educators and learners, and therefore it takes a comfortable and pleasant atmosphere in living it. One effort to create such process is with the selection of models and means of learning in accordance with the character of the course and target of learning.Â Scientific Writing Guidance (Bimbingan Penulisan Karya Ilmiah/BPKI) is a fourth semester course on Television and Film Study Program, Department of Recorded Media Art, Faculty of Art and Design, Indonesian Institute of the Arts at Surakarta. This classroom action research that combines Inquiry learning methods and Drilling used Facebooksocial media as a means of learning.Â This was used not as a medium for disseminating face-to-face material but as a media to upload student learning outcomes. The action cycle was implemented twice. The results of this study showed an average increase in the value of learning outcomes by 40% and very high learning motivation.Â Keywords: Inquiry, Drilling, Facebook